Psychosocial Adaptation among Adolescent Mothers in Western Kenya: The Role of Antenatal Care Counseling - Ibworo, Anne; Owenga, Jane; Omondi, Dickens; Omondi, Elizabeth (Journal of Advanced Psychology, 2024)
Purpose: This study sought to establish the influence of antenatal care counseling on psychosocial adaptation among adolescent mothers in Western Kenya and informed the development of a framework that would enhance psychosocial adaptation. Method: This health facility-based cross-sectional study was founded on Lazarus and Folkman’s psychosocial coping theory (1986) and Livneh’s psychosocial adaptation to chronic illness and disability framework (2001). It was conducted in three purposively selected County referral hospitals in Western Kenya among 438 sequentially selected adolescent mothers (10-19 years) who had visited antenatal care clinics during antenatal period. Frequency distribution and chi-square analysis were performed to test associations, and correlation (according to Cohen’s guideline of 1988) was included to determine the effect size of counseling provided. Moreover, Multinomial logistic regression (MLR) was run to determine the level of prediction of the variables to psychosocial adaptation (PSA). Results: Findings indicted that counseling provided for adolescent mothers in Western Kenya did not translate to significant levels of psychosocial adaptation. Specifically, while addressing depression, anxiety child irresponsiveness, and school dropout were significantly associated with respective psychosocial adaptation (p< 0.05), they were weakly correlated (r <.3) and among technical skills employed, only responsiveness and assurance were found to be moderately corelated with self-esteem (r> .3, p< 0.05). Significant predictive variables for the outcome (PSA) from chi square analysis and MLR, occurred singly and not in combination. They included; statistically significant relationship between provision of counseling on child irresponsiveness (x=9.26, df= 1, p=0.002); empathy (x= 5.69, df=1, p=0.017); responsiveness (x= 5.69, df=1, p = 0.005) and self-esteem, while responsiveness (x=17.5, df= 2, p=0.001) and clarity (x= 8.54, df= 2, p <0.014) were significantly associated with societal interaction. In addition, counselling adolescent mothers on acceptance and taking up maternal responsibilities (x=33.12, df=4, p<0.05); assurance (x=10.27, df=4, p=0.036) and responsiveness (x=28.64, df=4, p< 0.05) were found to be significantly associated with love and embrace for child among adolescent mothers. Moreover, Responsiveness exhibited by healthcare workers (HCWs) significantly contributed to love and acceptance for the child (OR, 2.1; 95%CI 0.6 -6.8) and child welfare clinic utilization (OR, 1.7; 95%CI 0.3- 9.2) among adolescent mothers. Recommendations: Adolescent mothers need individualized and targeted counseling to enhance psychosocial adaptation and which should be integrated into routine antenatal care.